2005
DOI: 10.3171/jns.2005.102.s_supplement.0185
|View full text |Cite
|
Sign up to set email alerts
|

Gamma knife surgery for trigeminal neuralgia: improved initial response with two isocenters and increasing dose

Abstract: Gamma knife surgery is an effective therapy for TN. Initial response rates appear to correlate with the number of shots and dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…3 Only five patients (8%) experienced mild facial numbness from the treatment. Thus, GKS remains an important treatment modality in patients with both MS and TN, and studies are needed to determine whether this group of patients should receive modified treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…3 Only five patients (8%) experienced mild facial numbness from the treatment. Thus, GKS remains an important treatment modality in patients with both MS and TN, and studies are needed to determine whether this group of patients should receive modified treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…A higher integral dose can be augmented either using of two isocenters or using of plugs. Morbidini-Gaffney (Morbidini-Gaffney, 2006) and Alpert (Alpert, 2005) found better pain control using two isocenters, Conversely Flickinger ) in a randomized prospective study found no differences using one or two isocenters and Fountas (Fountas, 2007) reports no differences using one, 2 or 3 isocenters. Nevertheless, nerve dysfunction was more important in the group of patients treated with multiple isocenters.…”
Section: Higher Dose Received By the Brainstemmentioning
confidence: 99%
“…For the analysis of the maximal dose delivered (in the range of 70 to 90 Gray), Many authors (Alpert, 2005;Kim, 2010;Longhi, 2007;Massager, 2007b;Morbidini-Gaffnay, 2006;Regis, 2009;Park, 2011;Shaya, 2004), communicate that using a maximal prescribed dose in the range of 80 to 90 Gray the patients response is better compared with treatment with a lower dose. On the other hand, other authors communicated that maximal dose of irradiation is not a prognostic factor (Aubuchon, 2010;Azar, 2009;Brisman, 2004;Dellaretti, 2008;Hayashi, 2009;Little, 2008;Longhi, 2007;Park, 2011;Petit, 2003;Riesenburger, 2010;Rogers, 2000;Young, 1998;).…”
Section: Maximal Dose Administered To the Nervementioning
confidence: 99%
“…A number of radiosurgery treatment-related factors have been evaluated to determine their influence on clinical outcomes. These include radiation dose, length of irradiated nerve, proximity of the isocenter to the brainstem, and the trigeminal nerveblood vessel relationship (2,(9)(10)(11)(12). Escalating the treatment dose or treating a longer section of the nerve results in a significantly higher rate of permanent trigeminal nerve dysfunction and no significant increase in duration of pain relief (9, 12).…”
Section: Introductionmentioning
confidence: 99%